[Christmas drawing and a sketch of a ship] - William F. Cody:::::::::
A small boy in pajamas is holding a candle as he looks at Christmas toys and presents. A wreath and Christmas stocking hang in front of him. On the reverse side is a small sketch of a wooden-mast ship approaching an unfinished bridge.